Localization, obstacle avoidance planning and control of a cooperative cable parallel robot for multiple mobile cranes. (August 2015) - Zi, Bin; Lin, Jun; Qian, Sen
Abstract: This paper addresses the cooperative problems in terms of localization, obstacle avoidance planning and automatic leveling control for a cable parallel robot for multiple mobile cranes (CPRMCs). The design model of the CPRMCs is elaborated on. The three-dimensional grid map method is utilized to plot the environment map based on the operation environment model. By combining the relative localization method with the absolute localization method, a cooperative localization scheme of the CPRMCs is developed, and an improved localization algorithm is designed on the basis of multilateration method. Then, according to the grid-based artificial potential field method, a global path planning of the CPRMCs is performed. Considering the possible collision of the single mobile crane, the sensor technology is applied to the cooperative obstacle avoidance. In addition, a four-point collaborative leveling method is adopted for automatic leveling control of the platform of the CPRMCs. Finally, the effectiveness of the CPRMCs system is verified through simulations. Highlights: Cable parallel robots for multiple mobile cranes are designed. Localization analysis of the robots are reported. Obstacle avoidance planning and automatic leveling control are performed. Illustrative simulation studies highlight the performance of the robots.